Pengaruh Tinopal terhadap Patogenisitas Nucleopolyhedrovirus pada Spodoptera litura - Ma'unah Ambarwati; Arman Wijonarko; Sedyo Hartono (Universitas Gadjah Mada, 2010)
Susceptibility of the armyworm, Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) to nucleopolyhedrovirus was evaluated using droplet feeding methods. S. litura was originally collected from the field in Bantul and has been reared continuously in the laboratory using artificial diet. The tested instars were exposed a series concentration of nucleopolyhedrovirus (2×103, 2×104, 2×105, 2×106, 2×107, 2×108, 2×109 PIB/ml) which were added with Tinopal 0,5% and 1%. The result indicated that the larval mortality of 3rd, 4th, and 5th instars Tinopal, significantly different with the addition of 1% Tinopal. This addition increased the effectiveness of NPV for 235, 25117, and 6.6 million fold. The observation of the larval midgut which was treated by Tinopal, showed that Tinopal physically disrupt the peritrophic membrane. Therefore, it can be suggested that the Tinopal facilitates the entry of NPV to the host insect.